HUBUNGAN PERILAKU MAKAN DENGAN STATUS GIZI PADA REMAJA PUTRI DI SMK NEGERI 1 PALU - Afrina Afrina (Citra Bangsa University - Literacy and Publishing Center (CBU-LPC), 2019)
Nutritional balance can be achieved by each person so it must consume at least one type of food from each class of food ingredients, namely carbohydrates, animal and vegetable protein, vegetables, fruits and milk. Unhealthy eating behavior will have an impact on health status in the short and long term. This study aims to analyze the relationship of eating behavior with nutritional status in girls in SMK Negeri 1 Palu. This type of quantitative research is analytic research with a cross sectional approach. The population in this study were all young women of class X and XI in SMK Negeri 1 Palu, totaling 740 people. The sample size of 111 people using the proportionate stratified random sampling technique. The results of the study were analyzed using univariate and bivariate analysis. The results showed that most of the respondents with eating behavior who were not at risk of eating disorders were 82 respondents 73.9%, most of them were respondents who had normal nutritional status which amounted to 73.0%. Chi Square test results obtained p value = 0,000 (5 0,05), this means statistically there is a relationship between eating behavior and nutritional status in adolescent girls. Conclusion: there is a relationship between eating behavior and nutritional status in young women. For adolescents, especially young women, to consume a variety of foods with balanced nutrition, and can be used as a source of youth knowledge about good eating behavior and balanced nutritional status. Keywords: eating behavior, nutritional status, adolescent girls.